Hypervirulence Markers Among Non-ST11 Strains of Carbapenem- and Multidrug-Resistant Klebsiella pneumoniae Isolated From Patients With Bloodstream Infections - Shen, Ping; Berglund, Björn; Chen, Yong; Zhou, Yanzi; Xiao, Tingting; Xiao, Yonghong; Zhou, Kai (Frontiers in Microbiology, 2020)
Multidrug-resistant Klebsiella pneumoniae and hypervirulent K. pneumoniae (hvKP) have traditionally been considered two individual populations, however, strains displaying both phenotypes have emerged during the recent decade. Understanding the genotypic and phenotypic basis of the convergence could be of clinical importance. In this study, we tried to evaluate the pathogenicity associated with different combinations of genotypes (i.e., sequence types, virulence factors, and capsular serotypes) and phenotypes (i.e., hypermucoviscousity and drug susceptibility) in K. pneumoniae. A total of 11 K. pneumoniae isolates causing bloodstream infections were included in the study, and they were assigned to seven STs (ST23, ST15, ST268, ST660, ST86, ST65 and ST1660) and carried various K-loci (KL1, KL2, KL16, KL20 and KL24). Hypermucoviscousity was observed for six isolates. blaKPC-2 was detected in six carbapenem-resistant isolates, and the remaining ones were either multidrug-resistant or resistant to two types of antibiotics. Aerobactin- and yersiniabactin-encoding genes were detected in all isolates. Although rmpA2 was detected in all isolates, most contained frameshift mutations (82%). Genes encoding salmochelin, RmpA, and PEG344 were detected in seven isolates. Colibactin-encoding genes were carried by six isolates. Discrepancies among measured virulence in Galleria mellonella and the serum-killing assay, and genotypes and phenotypes were detected. The results illustrate the complexity and difficulty with the current knowledge of hypervirulence to predict the phenotype by using genetic and phenotypic markers. Additionally, the emergence of carbapenem resistance via blaKPC-2 in two isolates of hvKP of different sequence types emphasizes the urgency with which reliable clinical diagnostics for hvKP is needed.